ATTENDANCE SYSTEM BASED ON RADIO FREQUENCY IDENTIFICATION TECHNOLOGY - Saleh Hassan, Abbas; Talal Hussein, Raoof; Kadhum Abboud, Izz (Journal of Engineering and Sustainable Development, 2015)
Attendance is an important aspect in every educational institute or workplace. Most universities are still using the paper based attendance system. This paper presents an effective approach to improve the processes of attendance system using Radio Frequency Identification (RFID) technology.The design of software tools was implemented by using Visual Basic 6.0 for interfacing and a database for persons’ information include RFID tags identification (IDs). The proposed design has Liquid Crystal Display (LCD) to get message from the application when the identification is done, and pass information back to the micro controller to send this information to LCD to be displayed.